“A Semantics Analysis of Denotative and Connotative Meaning in the Song Lyric ‘You’ll Be in My Heart’ by Phil Collins” - Naomi Arta Tambunan; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the denotative and connotative meanings found in the song lyric “You’ll Be in My Heart” by Phil Collins, featured in the Disney movie Tarzan. Using a qualitative descriptive method with a semantic approach based on the theory of Geoffrey Leech, the data were collected through documentation of words, phrases, and sentences in the lyric. The findings show 20 selected data, with 14 indicating denotative meaning and 19 indicating connotative meaning, revealing that many expressions contain both simultaneously. Literal expressions such as “take my hand” and “stop your crying” represent observable actions, while symbolic expressions such as “you’ll be in my heart” and “bond between us” convey emotional attachment, protection, and unconditional love. The study concludes that song lyrics function as literary texts rich in semantic layers, where simple language conveys deep emotional and social messages through the interaction of denotative and connotative meanings.